A Review on Effects of Operating Parameters in Batch and Column Mode for Adsorption of Methyl Violet Dye - Memon, Shehzad S.; Topare, Niraj S.; Bokil, Shantini A.; Shinde, Shambala Gadekar-; Khedkar, Satish V.; Khan, Anish (International Journal of Membrane Science and Technology, 2023)
Direct discharge of industrial effluents without treatment into natural sources poses a significant risk to the environment. Dye compounds are toxic and difficult for nature to process, causing serious physiologic harm to all organisms that come into contact with them. Water quality is directly impacted by the presence of methyl violet (MV) dye pigments as it reduces the photosynthetic activity of the streams, so it is crucial to eliminate it. Adsorption is generally accepted as a reliable method for getting rid of dye in wastewater. In most cases, the adsorption process is aided by the mutually beneficial interactions between the adsorbent, the dye, and the adsorption environment. This review highlights current scenarios of MV removal by various low-cost, eco-friendly adsorbents, and their efficiency. The removal of MV is examined in depth in this review paper, which discusses a variety of batch and column adsorption design experiments. Several parameters influence the adsorption process, which is the foundation of all laboratories looking for the best conditions. The primary goal of this review is to provide current information on the most researched affecting factors for batch and column operating modes. Flow rate, dye concentration, and bed height are all parameters in column adsorption investigations and contact time, pH, temperature, particle size, agitation speed, and adsorbent dose were all compiled for batch adsorption investigations and summarized in this review.